2006
DOI: 10.2174/187152306778772793
|View full text |Cite
|
Sign up to set email alerts
|

The Mast Cell Pathway to Inflammation and Homeostasis: Pharmacolo- gical Insights

Abstract: Mast cells (MCs) were first described by Paul Ehrlich as well fed granular cells that stain metachromatically. Today MCs are regarded as multifunctional, granulated, tissue-dwelling cells distributed in the perivascular spaces and connective tissues of every major organ of the body. Their long recognized phenotypic diversity might be associated not only with their anatomic distribution and mediator repertoire, but also with their functional characteristics related to the regulation of effector pathways. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
14
0
6
Order By: Relevance
“…In its natural environment, this symbiotic microorganism of the gastrointestinal flora (Guarner and Malagelada 2003) elicits a chemotactic response that plays a pivotal role in bacterial homeostasis, pathogenesis and survival against host defense mechanisms (Verstraeten et al 2008;Jean St et al 2008). Histamine and polyamines have been reported to enable pathogenic bacteria to overcome these mechanisms (Crosa and Walsh 2002), while histamine that is a key mediator of gastric acid secretion may modulate adaptation of pathogens to drug therapies often via TCS (Hori et al 2002;Guarner and Malagelada 2003;Kakavas et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In its natural environment, this symbiotic microorganism of the gastrointestinal flora (Guarner and Malagelada 2003) elicits a chemotactic response that plays a pivotal role in bacterial homeostasis, pathogenesis and survival against host defense mechanisms (Verstraeten et al 2008;Jean St et al 2008). Histamine and polyamines have been reported to enable pathogenic bacteria to overcome these mechanisms (Crosa and Walsh 2002), while histamine that is a key mediator of gastric acid secretion may modulate adaptation of pathogens to drug therapies often via TCS (Hori et al 2002;Guarner and Malagelada 2003;Kakavas et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the MC membrane stabilizer disodium cromoglycate (DSCG) has been reported to act via mobilisation of Ca 2+ and possibly Cl - [8] and to prevent C48/80-induced mediator release in a number of cases [9]. MCs being key cells in allergic and inflammatory responses are essential source of histamine and their function is tuned by histamine [10]. It has been shown that H 4 receptor activation induces Ca 2+ mobilization in MCs and mediates their migration towards histamine but has no effect on degranulation [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular tissues have a complete array of immune cells, including MCs, that interact with offending antigens and the external eye, in particular the eyelids and the bulbar conjunctiva, represents an ideal site for hypersensitivity reactions [20]. MCs may be activated by IgE-dependent or by non-immunological stimuli and by basic polyamines, such as C48/80, to release key preformed mediators, including histamine, which mediates its biological functions through its four pharmacologically distinct histamine receptors of the Gprotein-coupled receptor family [10,21]. Of these, H 1 and H 4 receptors are largely implicated in the inflammatory and immune responses and therefore they have been proposed to be useful for treating related disorders [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is also found in central neurons and cells in the cartilage [1]. After a variety of inflammatory stimuli, including bacterial products such as lipopolysaccharides (LPS), mast cells release mediators which lead to inflammatory and hypersensitivity responses.…”
Section: Introductionmentioning
confidence: 99%